Traditional knowledge and the challenges of its legal protection in Argentina (Quinto Sol, 2013)
Legal protection of accumulated and transgenerational developedknowledge by indigenous peoples and local communities, especiallythose associated with the properties, uses and characteristics of biologicaldiversity, raises some issues and uncertainties. The Intellectual PropertyLegal Regimen in force, which establishes the basis for the protectionof an individual author’s work, and the Patent System are not able toprotect collective traditional knowledge.The aim of this paper is to discuss not only the limitations that exist in the Argentine legal system to protect them adequately, but also the challengesinvolved, including from practical problems of registration to deeperissues related to the nature of traditional knowledge and the difficultiesto design effective mechanisms to respect the worldview, culture andcustomary law of the peoples involved and able to prevent their use forcommercial applications.
Keywords: traditional knowledge; intangible heritage; legislation